2000
DOI: 10.3794/ijme.11.c
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Experience of Students in Middlesex University Business School (MUBS): Why do they enjoy some modules/lectures and dislike others?

Abstract: The context of teaching in higher education has changed rapidly in the last decade. The purpose of this paper is to explore what students today really want, what they expect of the lecturers and why they prefer some modules or courses but dislike others. Specifically, the study looks at the learning benefits of lecturing as 'good education' context vs. lecturing as 'entertainment' context. Overall, thirty seven focus groups were convened within Middlesex University Business School. It was found that students s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It is the ability to motivate students through being enthusiastic and entertaining (Heffernan et al, 2009;Barnes & Lock, 2010). According to Jin (2000) a dynamic lecturer is one who is interesting, charismatic and humorous. Research has revealed that dynamic delivery entails preparing students for examinations giving clear explanations, using good examples, varying delivery methods, using students' native language discreetly (Grieniel-Fuhrmann, 2003;Rammal, 2006;Xiao, 2006).…”
Section: Important Lecturer Attributesmentioning
confidence: 99%
“…It is the ability to motivate students through being enthusiastic and entertaining (Heffernan et al, 2009;Barnes & Lock, 2010). According to Jin (2000) a dynamic lecturer is one who is interesting, charismatic and humorous. Research has revealed that dynamic delivery entails preparing students for examinations giving clear explanations, using good examples, varying delivery methods, using students' native language discreetly (Grieniel-Fuhrmann, 2003;Rammal, 2006;Xiao, 2006).…”
Section: Important Lecturer Attributesmentioning
confidence: 99%